Do You Remember the Sixties?: The Scholarship of Resistance and Rebellion - Lexier, Roberta (Labour / Le Travail, 2010)
The article reviews two books: "New World Coming: The Sixties and the Shaping of Global Consciousness," edited by Karen Dubinsky, Catherine Krull, Susan Lord, Sean Mills, and Scott Rutherford, and "Canada's 1960s: The Ironies of Identity in a Rebellious Era" by Bryan D. Palmer.
Keywords: BOOKS -- Reviews; CANADA'S 1960s: The Ironies of Identity in a Rebellious Era (Book); DUBINSKY, Karen; KRULL, Catherine; LORD, Susan; MILLS, Sean; NEW World Coming: The 60s & the Shaping of Global Consciousness (Book); Nonfiction; PALMER, Bryan D.; RUTHERFORD, Scott